An integrative biological assessment of the programming effects of glucocorticoids upon the developing brain : insights on their relevance for future psychiatric pathologies - Mesquita, Ana Raquel Marcelino (2008)
Tese de Doutoramento em Ciências da Saúde – Ciências Biológicas e Biomédicas